Body mass change and ultraendurance performance: A decrease in body mass is associated with an increased running speed in male 100-km ultramarathoners - Rüst, C. A.; Knechtle, B.; Knechtle, P.; Wirth, A.; Rosemann, T. (The Journal of Strength and Conditioning Research, 2012)
We investigated, in 50 recreational male ultrarunners, the changes in body mass, selected hematological and urine parameters, and fluid intake during a 100-km ultramarathon. The athletes lost (mean and SD) 2.6 (1.8) % in body mass (p < 0.0001). Running speed was significantly and negatively related to the change in body mass (p < 0.05). Serum sodium concentration ([Na+]) and the concentration of aldosterone increased with increasing loss in body mass (p < 0.05). Urine-specific gravity increased (p < 0.0001). The change in body mass was significantly and negatively related to postrace serum [Na+] (p < 0.05). Fluid intake was significantly and positively related to both running speed (r = 0.33, p = 0.0182) and the change in body mass (r = 0.44, p = 0.0014) and significantly and negatively to both postrace serum [Na+] (r = -0.42, p = 0.0022) and the change in serum [Na+] (r = -0.38, p = 0.0072). This field study showed that recreational, male, 100-km ultramarathoners dehydrated as evidenced by the decrease in >2 % body mass and the increase in urine-specific gravity. Race performance, however, was not impaired because of the loss in body mass. In contrast, faster athletes lost more body mass compared with slower athletes while also drinking more. The concept that a loss of >2% in body mass leads to dehydration and consequently impairs endurance performance must be questioned for ultraendurance athletes competing in the field. For practical applications, a loss in body mass during a 100-km ultramarathon was associated with a faster running speed.